KATA ULANG BAHASA MELAYU DIALEK SANGGAU - Susana, Warsih Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research focused on Malay  language of Sanggau dialect that is the repetition words of Malay  language of Sanggau dialect. Malay  language of Sanggau dialect is a language used by the Sanggau Malay community to communicate in daily life. The problems in this research were how the form of repetition words, category of repetition words, and the meaning of repetition words in Malay  language of Sanggau dialect. The purposes of this research were to describe the form of repetition words, category of repetition words, and the meaning of repetition words in Malay  language of Sanggau dialect. This research used descriptive method with qualitative form. The source of this research data is  Malay language of Sanggau dialect used by informants that contain the repetition words. The techniques used are interview, trace technique, and observation. Data collection tools were lists of interview questions, pictures lists, and voice recorders. Based on the data analysis of Malay  language of Sanggau dialect repetition words, the researcher found four repetition words namely: repetition of whole words, partial repetition words, repetition of affixed, and repetition sound changes. There were five category of repetitions namely: nouns, adjectives, verbs, adverbs, and numerical. Keywords: Morfologi, Repetition Words, Sanggau Dialect.